2020
DOI: 10.1590/0074-02760200287
|View full text |Cite
|
Sign up to set email alerts
|

Dengue diagnostics: serious inaccuracies are likely to occur if pre-analytical conditions are not strictly followed

Abstract: BACKGROUNDThe heat-labile nature of Dengue virus (DENV) in serum samples must be considered when applying routine diagnostic tests to avoid issues that could impact the accuracy of test results with direct implications for case management and disease reporting.OBJECTIVES To check if pre-analytical variables, such as storage time and temperature, have an impact on the accuracy of the main routine diagnostic tests for dengue.METHODS Virus isolation, reverse transcription real-time polymerase chain reaction (RT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…In the early stages of the disease (seven or less than 7 days after onset of illness), DENV infection can be diagnosed from serum, plasma, circulating blood cells, or from other tissues by detecting viral RNA with nucleic acids amplification tests, NS1 protein using some commercial tests and viral isolation in mammalian or mosquito cell culture to further genotyping and lineage for virus characterization [122]. DENV is thermally labile; RNA detection and isolation of the virus are highly dependent on well-preserved specimens for accurate diagnosis results [127]. The samples awaiting shipment to the laboratory should be stored in a refrigerator or freezer.…”
Section: Diagnosis and Control Of Denv Infectionmentioning
confidence: 99%
“…In the early stages of the disease (seven or less than 7 days after onset of illness), DENV infection can be diagnosed from serum, plasma, circulating blood cells, or from other tissues by detecting viral RNA with nucleic acids amplification tests, NS1 protein using some commercial tests and viral isolation in mammalian or mosquito cell culture to further genotyping and lineage for virus characterization [122]. DENV is thermally labile; RNA detection and isolation of the virus are highly dependent on well-preserved specimens for accurate diagnosis results [127]. The samples awaiting shipment to the laboratory should be stored in a refrigerator or freezer.…”
Section: Diagnosis and Control Of Denv Infectionmentioning
confidence: 99%
“…Tests such as RT-PCR and viral isolation showed a greater dependence on well-preserved samples to make an accurate diagnosis. Their results showed that storage of samples for 15 days at -30°C yielded inaccurate results in RT-PCR and viral isolation tests, while in the same samples the NS1 ELISA tests did not show a significant reduction in positivity (46). In favor of the hypothesis of sample quality deterioration due to transportation, this study shows that the samples that remained at the local level for viral culture processing gave positive results for virus isolation and subsequent genomic sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…As an RNA virus, DENV is labile and sensitive to deterioration, which is advantageous in reducing the risk of contamination in laboratory assays, but can reduce the sensitivity of molecular assays if pre-analytical handling is inappropriate [16]. A 37% reduction in specimens testing RT-PCR positive after 48 h storage refrigerated at 2–8 °C was observed, and and 20 % reduction after 15 days storage at −30 °C [39]. Whichever specimen is chosen, appropriate handling is required to optimize yield.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Specimens are sensitive to pre-analytical handling, which impacts sensitivity. A significant decrease in culture detection of virus from serum was noted with 24 h of refrigerator storage or 15 days of freezing at −30 °C, when compared to immediate processing after retrieval from liquid nitrogen storage [39]. Because of this, many studies now use molecular assays as a gold standard instead.…”
Section: Virus Isolationmentioning
confidence: 99%